VO#037 Quotation for additional UPVC components in plumbing works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of price quotation for additional UPVC components in plumbing works of BRACU new campus project.